Study of Lipids Profile Levels in Patients with Hypothyroidism in Al-Muthanna Province - Duaa Hamad Hamza (Journal of Global Pharma Technology, 2016)
The objective of this study was to investigate the changes that occurred on lipids profile levels of patients with hypothyroidism in al-muthanna province. The current study is carried out in the ‘specialized center of endocrinology and diabetes’ in Al- Muthanna province. The study included 200 individuals (100 patients with hypothyroidism and 100 controls).The patients and control divided to three groups according to ages. The ages were between (20-49) years. The results show a significant increase at(P<0.05) in ( Total cholesterol (TC), Triglyceride (TG), high-density lipoprotein (HDL), low-density lipoprotein (LDL) and very low density lipoproteins (VLDL) levels of patients comparing with control group in all age groups .In this study concluded that hyperlipidemia is associated with hypothyroidism. These enhance the risk for development of atherosclerosis and coronary artery disease.Keywords: Hypothyroidism, Total cholesterol, Triglyceride, High-density lipoprotein, Low-density lipoprotein, Very low density lipoproteins.